Dimensional analysis of the adequacy of agricultural machinery for biomass handling in agroforestry systems - de Morais, Gelton F.; Han, Daniela; da S. G. Santos, Jenyffer; Ramos, Luiz O.; Xavier, Marcelo G. B.; Schimidt, Leonardo; de Souza, Hugo T. [UNESP]; de Castro, Fernanda T.; Garcia, Angel P.; Albiero, Daniel (FapUNIFESP (SciELO), 2025)
ABSTRACT Agroforestry Systems (AFS) integrate trees, agronomic crops and forage species, focusing on agricultural sustainability and productivity. However, the lack of specific mechanization for AFS limits their efficiency. This research aimed to assess the adequacy of existing agricultural machinery for biomass handling in AFS and thus contribute to solving the issue of lack of specific mechanization in AFS for family farming, in order to foster the expansion of AFS lands. This study assessed three types of machinery for handling Mombaça grass (Megathyrsus maximus Jacq): coastal brushcutter (CBC), tractor-mounted rotary brushcutter (RBC), and mini grain reaper machine (GRM) throughout three cutting cycles. The dimensional analysis and Likert scale methods were employed for assessment of cutting height, handling time, labor cost, fuel consumption, regrowth speed, dry matter weight, and raking time of cut grass. Obtained through dimensional analysis, Pi-terms Π1 and Π3 represent, respectively, the treatment’s quality of cut and financial cost. The binomial Π1 × Π3 represents the cost-benefit ratio. CBC was suitable for small areas, to guarantee better grass regrowth rate, and higher biomass production, while providing the best cost-benefit ratio for fuel. GRM was the most adequate for obtaining the lowest operational costs, the lowest time required for raking up cut grass, higher biomass production, providing the best financial estimate for fuel. RBC was indicated for faster work, handling at higher scales, and considerably reduced physical strain. RESUMO Sistemas Agroflorestais (SAFs) integram árvores, culturas de interesse agronômico e forrageiras, visando sustentabilidade agrícola e produtividade. Contudo, a falta de mecanização específica para SAFs limita sua eficiência. Esta pesquisa objetivou avaliar a adequação das máquinas agrícolas no manejo da biomassa em SAFs e contribuir para a solução do problema da falta de mecanização específica para SAFs cultivados pela agricultura familiar. O estudo avaliou três tipos de máquinas para o manejo do capim Mombaça (Megathyrsus maximus Jacq): roçadora costal (CBC), roçadora rotativa montada ao trator (RBC) e mini colhedora de grãos (GRM) ao longo de três ciclos de corte. Os métodos da análise dimensional e escala Likert foram empregados para a avaliação da altura de corte, tempo de manejo, custo de mão de obra, consumo de combustível, velocidade de rebrota, peso de matéria seca e tempo de amontoa. Os Pi-termos Π1 e Π3 representam, respectivamente, a qualidade do corte e o custo financeiro. O binômio Π1 × Π3 representa a relação custo-benefício. A CBC foi adequada para pequenas áreas, garantindo melhor vigor de rebrote, maior produção de biomassa e expressou a melhor relação custo-benefício. A GRM foi indicada para obter os menores custos operacionais, o tempo mais rápido necessário para amontoar o capim cortado, a maior produção de biomassa e a melhor previsão financeira de custo com combustível. A RBC foi adequada para realizar o trabalho mais rapidamente, para manejo em escalas maiores e para reduzir consideravelmente o esforço físico.